2020
DOI: 10.1371/journal.ppat.1008689
|View full text |Cite
|
Sign up to set email alerts
|

Long-term persistence of infectious Zika virus: Inflammation and behavioral sequela in mice

Abstract: The neurodevelopmental defects associated with ZIKV infections early in pregnancy are well documented, however the potential defects and long-term consequences associated with milder infections in late pregnancy and perinatal period are less well understood. To model these, we challenged 1 day old (P1) immunocompetent C57BL/6 mice with ZIKV. The animals developed a transient neurological syndrome including unsteady gait, kinetic tremors, severe ataxia and seizures 10–15 days post-infection (dpi) but symptoms s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 55 publications
4
60
0
Order By: Relevance
“…Persistence of SARS-CoV-2 in some patients with PASC symptoms is not unexpected. The literature is replete with examples of single-stranded RNA virus persistence, spanning decades of research on samples obtained from living human patients, autopsy studies, and animal studies ( Viola et al, 1978 ; Riddell et al, 2007 ; Doi et al, 2016 ; Randall and Griffin, 2017 ; Ireland et al, 2020 ). Persistence of single-stranded RNA viruses in the central nervous system has been documented on multiple occasions.…”
Section: Sars-cov-2 Appears Capable Of Persistence In Certain Tissuesmentioning
confidence: 99%
“…Persistence of SARS-CoV-2 in some patients with PASC symptoms is not unexpected. The literature is replete with examples of single-stranded RNA virus persistence, spanning decades of research on samples obtained from living human patients, autopsy studies, and animal studies ( Viola et al, 1978 ; Riddell et al, 2007 ; Doi et al, 2016 ; Randall and Griffin, 2017 ; Ireland et al, 2020 ). Persistence of single-stranded RNA viruses in the central nervous system has been documented on multiple occasions.…”
Section: Sars-cov-2 Appears Capable Of Persistence In Certain Tissuesmentioning
confidence: 99%
“…It is not surprising that longer duration of acute ZIKV infections can lead to greater inflammation and thereby, increased pathology. Studies in mouse models have shown that long-term persistance of ZIKV in the brain can lead to inflammation and increased risk of neuropathology [60].…”
Section: Discussionmentioning
confidence: 99%
“…Often, when entering the brain, these viruses cause acute encephalitis. Nevertheless, they can persist in the brain [ 151 , 152 , 153 , 154 ]. However, there is paucity of knowledge about chronic effects of persisting virus in the brain and corresponding neuroinflammation.…”
Section: Virus Infection In the Brainmentioning
confidence: 99%
“…Measles virus: [ 135 , 202 , 203 ]. Japanese encephalitis virus (JEV): [ 100 , 151 , 153 , 155 ]. Zika virus (ZIKV): [ 143 , 146 , 148 ].…”
Section: Tablementioning
confidence: 99%